Human Resource Development in Government Civil Apparatus in the Republic of Indonesia - Maspero Situngkir (STAATSRECHT: Indonesian Constitutional Law Journal, 2020)
Abstract:Human Resources is a very important factor and a driving force in an organization. Without qualified human beings who are capable of being the activator, an organization cannot run properly and it will even stop. To produce every product, creative and innovative people are needed. Behind the production of every product or service are human thoughts, efforts and human hours of work. The research method used in this research is a qualitative method with a literature approach. The data obtained were sourced from literature reviews, both from scientific journals and books. The result of the research states that Human Resources is an important thing in the government apparatus and must always be repaired and addressed.Keywords: Human Resources, Government Apparatus, Republic of Indonesia.